Repurposing of Proton Pump Inhibitors as first identified small molecule inhibitors of endo-β-N-acetylglucosaminidase (ENGase) for the treatment of NGLY1 deficiency, a rare genetic disease. Issue 13 (1st July 2017) - Bi, Yiling; Might, Matthew; Vankayalapati, Hariprasad; Kuberan, Balagurunathan
Graphical abstract: Abstract: N -Glycanase deficiency, or NGLY1 deficiency, is an extremely rare human genetic disease. N -Glycanase, encoded by the gene NGLY1, is an important enzyme involved in protein deglycosylation of misfolded proteins. Deglycosylation of misfolded proteins precedes the endoplasmic reticulum (ER)-associated degradation (ERAD) process. NGLY1 patients produce little or no N -glycanase (Ngly1), and the symptoms include global developmental delay, frequent seizures, complex hyperkinetic movement disorder, difficulty in swallowing/aspiration, liver dysfunction, and a lack of tears. Unfortunately, there has not been any therapeutic option available for this rare disease so far. Recently, a proposed molecular mechanism for NGLY1 deficiency suggested that endo -β- N -acetylglucosaminidase (ENGase) inhibitors may be promising therapeutics for NGLY1 patients. Herein, we performed structure-based virtual screening utilizing FDA-approved drug database on this ENGase target to enable repurposing of existing drugs. Several Proton Pump Inhibitors (PPIs), a series of substituted 1 H -benzo [ d ] imidazole, and 1 H -imidazo [4, 5- b ] pyridines, among other scaffolds, have been identified as potent ENGase inhibitors. An electrophoretic mobility shift assay was employed to assess the inhibition of ENGase activity by these PPIs. Our efforts led to the discovery of Rabeprazole Sodium as the most promising hit with an IC50 of 4.47 ± 0.44 μM. This is the first report that describes the discovery of small molecule ENGase inhibitors, which can potentially be used for the treatment of human NGLY1 deficiency.